Lithium ion battery with excellent rate capability and electric device
By designing and controlling the electrode sheets, the electrode material characteristics of lithium-ion batteries are optimized, and the poor performance of lithium-ion batteries under high-rate charging and discharge conditions is solved, achieving better dynamics and safety performance.
Patent Information
- Application Number
- CN202411748896.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-25
AI Technical Summary
Existing lithium-ion batteries perform poorly under high-rate charging and discharging conditions, resulting in long charging time and insufficient discharge power, limiting their application in electric vehicles and consumer electronic products.
By designing and controlling the electrode sheet, lower high defect carbon and moderate carbon coating ratio are adopted to improve the interface stability of the electrode, optimize the Raman spectral characteristics, and achieve lower overpotential and better rate performance.
It achieves excellent performance of lithium-ion batteries under high-speed conditions, improves the battery's dynamic performance and safety performance, and meets the power requirements under high load operation.
Smart Images

Figure BDA0005164479910000061 
Figure BDA0005164479910000091 
Figure BDA0005164479910000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a battery and an electrical device with excellent rate performance. Background Art
[0002] In today's era of rapid technological development, lithium-ion batteries, as an indispensable energy storage device in modern life, have been widely used in many fields such as mobile phones, laptops, electric vehicles, etc. However, despite the significant progress in lithium-ion battery technology, its poor rate performance still exists, which greatly limits its application in more scenarios.
[0003] The so-called rate performance refers to the performance of the battery under high current charging and discharging conditions. When faced with high rate charging and discharging requirements, current lithium-ion batteries often have problems such as long charging time and insufficient discharge power. For example, in the field of electric vehicles, although lithium-ion batteries can provide sufficient driving range, they are unable to cope when fast charging or high power output is required. This not only affects the travel efficiency of users, but also limits the promotion of electric vehicles in more application scenarios.
[0004] In addition, in the field of consumer electronics, as people's requirements for device performance continue to increase, the demand for high-rate discharge is also increasing. However, existing lithium-ion batteries are difficult to meet these requirements, resulting in devices being prone to low power when running at high loads.
[0005] To solve this problem, researchers are actively exploring new battery materials and technologies. For example, by improving the structure and composition of electrode materials to increase the migration rate of lithium ions, and developing new electrolytes to enhance the stability of batteries under high temperature and high current conditions. Summary of the invention
[0006] In order to solve the technical problem of poor rate performance of existing batteries, a lithium-ion battery and an electrical device with excellent rate performance are provided. The present invention improves the interface stability of the electrode by designing the electrode sheet, adjusting it to have lower high-defect carbon and a moderate carbon coating ratio, so as to achieve optimal interface dynamic performance and lower overpotential, so that the battery has excellent rate performance.
[0007] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:
[0008] A lithium-ion battery with excellent rate performance, comprising a negative electrode plate, wherein the wave number of the negative electrode plate in the spectrum is 1000cm -1 ~2000cm -1 With P, P1, P2, and satisfying the following conditions:
[0009] ①1<P≤10;
[0010] ②0.1≤P1≤1;
[0011] ③1<P2≤P;
[0012] The definition of P is: at least 100 random point scans on the negative electrode are tested by Raman spectroscopy, thereby generating a corresponding number of Raman spectra, and calculating the peaks of each Raman spectrum at a wave number of 1000 cm -1 ~2000cm -1 The ratio of the strongest peak intensity value to the second strongest peak intensity value is recorded as Ra, and the corresponding number of Ra are summed and averaged to obtain P;
[0013] The definitions of P1 and P2 are: -1 ~2000cm -1 The ratio of the intensity value of the second strongest peak to the intensity value of the strongest peak is recorded as Ra1. The sum and average of the ratios in the range of 0.1≤Ra1≤1 is obtained to obtain P1; the sum and average of the ratios in the range of 1<Ra1≤P is obtained to obtain P2.
[0014] Furthermore, at the wave number of 1450 cm -1 ~1800cm -1 With P', the following conditions are satisfied: ④0≤P'≤P;
[0015] The definition of P' is: Calculate the corresponding number of the Raman spectra obtained above at the wave number 1450cm -1 ~1800cm -1 The ratio of the strongest peak intensity value to the second strongest peak intensity value is recorded as Rb, and the corresponding number of Rb's are summed and averaged to obtain P'.
[0016] Furthermore, when P'≠0, there are two position areas P1' and P2' with different P' values, and the following conditions are satisfied at the same time:
[0017] ⑤0≤P1'≤P1;
[0018] ⑥P1<P2'≤P2;
[0019] Wherein, the definitions of P1' and P2' are: Calculate the corresponding number of Raman spectra obtained above at the wave number 1450cm -1 ~1800cm -1 The ratio of the intensity value of the second strongest peak to the intensity value of the strongest peak is recorded as Rb1. The sum and average of the ratios in the range of 0≤Rb1≤P1 is obtained to obtain P1'; the sum and average of the ratios in the range of P1<Rb1≤P2 is obtained to obtain P2'.
[0020] Furthermore, assuming that the number of the at least 100 position areas of the point scan is n, then in the corresponding number of Raman spectra, the number of position areas that meet condition ② is x1, and the number of position areas that meet condition ③ is y1. The proportion of the number of position areas that meet condition ② is recorded as P1 q , the proportion of location areas that meet condition ③ is recorded as P2 q , then P1 q =(x1÷n)×100%, P2 q =(y1÷n)×100%, then the proportion of the number of location areas satisfies the following relationship: P1 q ≤P2 q ≤1.2×(1-P1 q -P2 q ).
[0021] Furthermore, assuming that the number of the at least 100 position areas of the point scan is n, then in the corresponding number of Raman spectra, the number of position areas that meet condition ⑤ is x2, and the number of position areas that meet condition ⑥ is y2. The proportion of the number of position areas that meet condition ⑤ is recorded as P1' q , the proportion of location areas that meet condition ⑥ is recorded as P2' q , then P1' q =(x2÷n)×100%, P2' q =(y2÷n)×100%, then the number of location areas satisfies the following relationship: P1' q +P2' q <50%.
[0022] Furthermore, the average charge overpotential of the negative electrode plate at a 1C rate is φ2, and φ2 satisfies the following relationship: 0<φ2≤0.5φ1;
[0023] Wherein, φ1 represents the average charge overpotential of a lithium-ion battery made with the negative electrode sheet at a 3C rate, and φ1 satisfies the following relationship: 0<φ1≤0.5V.
[0024] Furthermore, the negative electrode plate includes a negative electrode current collector and a negative electrode active material coating region and a negative electrode active material non-coating region located on at least one surface of the negative electrode current collector;
[0025] The negative electrode active material coating area is formed by coating and curing the negative electrode slurry. The negative electrode slurry includes a negative electrode active material, a dispersant, a binder and a conductive agent. The dispersant and the binder are conventionally selected and have little effect on the battery performance. The dispersant is carboxymethyl cellulose CMC, and the binder is polyacrylic acid compound, PVDF, SBR emulsion, etc. The selection and preparation method of the negative electrode active material and the selection of the conductive agent are more critical, which will produce unpredictable changes to the above parameters.
[0026] The negative electrode active material is selected from one or more of artificial graphite, natural graphite, mesophase carbon microspheres, hard carbon, soft carbon, and silicon-based materials (such as silicon-oxygen materials, silicon-carbon materials, etc.), and the surface of the negative electrode active material may or may not have a carbon coating layer;
[0027] The conductive agent is selected from one or more of conductive carbon black, carbon nanotubes, carbon nanofibers, graphite, graphene, graphene oxide, reduced graphene oxide, and fluorinated graphene.
[0028] Furthermore, the negative electrode slurry includes solid matter and a solvent, the solid content of the negative electrode slurry is in the range of 30wt%-60wt%, and the solvent can be water or other volatile organic solvents;
[0029] The solid material includes the following materials in 100% by weight: 94%-98.5% of negative electrode active material, 0.5%-2% of conductive agent, 0.5%-2% of dispersant, and 0.5%-2% of binder.
[0030] Preferably, the negative electrode active material includes 0%-35wt% of silicon-based material.
[0031] Furthermore, the negative electrode active material on the negative electrode plate is placed in an air atmosphere and calcined within 350°C. The weight of the negative electrode active material before calcination is M, and the weight of the negative electrode active material after calcination is M'. The loss amount of the negative electrode active material after calcination is m1=M-M', and the corresponding loss rate L=(m1÷M)×100%. The loss rate L satisfies the following relationship: 3%≤L≤20%.
[0032] Furthermore, the lithium-ion battery is a full-tab lithium-ion battery, which generally further includes a shell, a wound-body battery cell and an electrolyte, wherein the shell accommodates the battery cell and the electrolyte, and the battery cell is immersed in the electrolyte;
[0033] The battery cell is formed by winding a positive electrode sheet, a separator and a negative electrode sheet;
[0034] The positive electrode plate includes a positive electrode current collector and a positive electrode active material coating area and a positive electrode active material non-coating area located on at least one surface of the positive electrode current collector. Usually, the positive electrode active material is selected from one or more of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide, wherein nickel element accounts for at least 80wt% of the elements in the positive electrode active material.
[0035] To achieve the above lithium-ion battery with better performance, the negative electrode plate is the key. For example, the negative electrode active material in the negative electrode plate is selected to be a combination of the graphite and the silicon-based material, the proportion of the silicon-based material in the negative electrode active material is in the range of 0wt%-35wt%, and the surfaces of the graphite and the silicon-based material are respectively provided with a carbon coating layer, the carbon coating layer content on the graphite surface is in the range of 0%-8%, the carbon coating layer content on the silicon-based material surface is in the range of 2%-8%, the D50 particle size of the graphite is in the range of 9μm-50μm, and the D50 particle size of the silicon-based material is less than 8.5μm;
[0036] The conductive agent is selected from a combination of conductive carbon black and carbon nanotubes, wherein the conductive carbon black accounts for 0.5wt%-1.5wt% of the solid substance, and the carbon nanotubes account for 0.5wt% of the solid substance;
[0037] The negative electrode sheet is prepared by the following steps:
[0038] S1. Preparation of negative electrode slurry: premix the silicon-based material and the conductive agent in water, add the graphite and the dispersant, stir and mix at a low speed of 10-50 rpm, then add the carbon nanotubes and the binder, stir and mix at a low speed of 10-50 rpm, adjust the solid content within the range of 30 wt%-60 wt%, stir at a low speed of 10-50 rpm and disperse at a high speed of 500-2000 rpm for at least 1 hour;
[0039] S2. The negative electrode slurry is uniformly coated on the surface of the current collector, and the surface density of the single surface is 4-12 mg / cm after drying. 2 The compaction density is within the range of 1.4-1.8 g / cc. Within this range, the electrochemical performance and charge-discharge performance of the negative electrode sheet are relatively good, thereby forming a negative electrode active material coating area and a negative electrode active material non-coating area to obtain a negative electrode sheet;
[0040] S3, winding the positive electrode sheet, the separator and the negative electrode sheet to form a wound battery cell, placing it in a shell, injecting electrolyte, forming, and then aging at 50°C-70°C for 24h-48h to obtain a lithium-ion battery. The above part lists the selection combination and condition parameters with better performance, but does not exclude the selection combination of other substances and other parameter configuration conditions, and all formulas that meet the above Raman and other characteristic relationships are within the scope of the present invention.
[0041] The second aspect of the present invention provides an electrical device, comprising the lithium-ion battery described above, which may be a cylindrical battery, a square battery, etc.
[0042] Beneficial technical effects:
[0043] The present invention performs relevant design and regulation on the negative electrode sheet, including the selection and ratio of the negative electrode active material, the carbon coating ratio, and the selection and ratio of the conductive agent, so that the Raman spectrum of the obtained negative electrode changes, and the Raman spectrum of multiple position areas on the negative electrode is statistically analyzed to optimize the designed negative electrode formula;
[0044] Generally, the higher the graphitization degree of the carbon material, the smaller the interlayer spacing. G The larger the peak intensity, the greater the peak intensity. Both D peak and D' peak are characteristic peaks related to the defects of carbon materials. Usually, D peak is located at about 1350 cm -1 , representing the disorder-induced boundary vibration mode of the hexagonal Brillouin zone, while the D' peak usually appears at 1620 cm -1 The D' peak is about 100 points, which is related to the edge defects. Therefore, the D' peak is a peak related to the end face of the graphite structure, which can assist in judging the carbon structure of the surface layer. When the intensity of the D' peak is greater than the D peak intensity, it indicates that the end face of the designed material is too exposed, and the material may be broken more severely, thereby deteriorating the dynamics and safety performance. The present invention tests and statistically analyzes the Raman spectra of at least 100 points of the designed negative electrode. When the defects of the carbon material on the surface of the negative electrode are fewer, the I D The weaker the peak, the larger the P value becomes. At this time, the electrode has better electronic conductivity and ion conductivity, and has better high-rate performance in the range of 1<P≤10;
[0045] P1 is the area where the carbon with the most defects is located, while P2 is a characteristic of most coated carbons. Therefore, by adjusting the lower high-defect carbon and the appropriate coating carbon ratio, the best interface dynamics and interface stability can be achieved; too high a high-defect carbon will greatly reduce the interface safety, and 1-P1-P2 belongs to high-quality coated carbon and graphite carbon, which has a small carbon layer spacing and few defects, so the ion conductivity is low, and too high a proportion will reduce the dynamics; through the reasonable allocation of P1, P2, 1-P1-P2, while satisfying 0.1≤P1≤1, 1<P2≤P, the number of corresponding position areas of the negative electrode meets P1 q ≤P2 q ≤1.2×(1-P1 q -P2 q ), in addition, the end face of graphite may show P' signal in Raman response, wherein there are two different regions, P1' and P2', wherein P1' and P2' represent the regions where the end face of graphite is slightly exposed and heavily exposed, respectively. If the total amount of exposed positions of the end face of graphite exceeds 50%, the interface stability will be reduced, thereby causing potential safety hazards. Reasonable carbon layer content and structural design will be conducive to achieving optimal high-rate application performance, and enhancing the interface stability of the negative electrode and improving safety performance. Therefore, the negative electrode plate with phase parameters disclosed in the present invention can achieve the optimal solution for kinetic and safety performance design while achieving high-rate charge and discharge, so that the battery has better kinetics and lower overpotential, and excellent safety performance. DETAILED DESCRIPTION
[0046] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.
[0048] The experimental methods in the following examples without specifying specific conditions are usually measured in accordance with national standards; if there is no corresponding national standard, the method is carried out in accordance with the general standard requirements or general methods.
[0049] The expression "within the range" should be considered as not including the endpoint values.
[0050] The following appear: for example, the ratio of the strongest peak to the second strongest peak, which means the intensity value of the strongest peak divided by the intensity value of the second strongest peak; for example, the ratio of the second strongest peak to the strongest peak, which means the intensity value of the second strongest peak divided by the intensity value of the strongest peak.
[0051] Analytical methods
[0052] 1. Raman spectrum test: Take a fresh cylindrical battery, and after standing at 25℃ for 2h, fully discharge it with a small current of 0.2C, then disassemble it to get the negative electrode (or directly use the prepared negative electrode), and soak it in DMC for 12h, rinse it with DMC 3 times, dry it, and further bake it in a vacuum oven at 60℃ for 2h. The obtained electrode and its particles are scanned with a Raman instrument, and an excitation light of 532nm wavelength is selected (other settings including grating, confocal pinhole, slit, etc. can be set according to the conventional setting parameters in this field), and at least 100 points are randomly scanned (the following cases scan 100 test points), so each point will obtain a Raman spectrum, and these spectra are statistically analyzed.
[0053] The wavelength setting of the excitation light is not unique, and 514nm (green light) laser, 532nm solid laser, 632.8nm (red light) visible light laser, 780nm visible light laser, 785nm diode, 830nm near-infrared laser, etc. can all be used in the present invention. In theory, the peak position on the spectrum of the Raman spectrum has nothing to do with the wavelength of the excitation light of the laser, but if some samples produce strong fluorescence under the excitation of a certain wavelength laser, it will interfere with the Raman spectrum. At this time, it is necessary to replace the laser of other excitation light to avoid interference caused by fluorescence. If the sample does not have fluorescence under different excitation lights, it can be used regardless of the wavelength of the excitation light.
[0054] The meanings of the various symbols involved in the Raman spectroscopy test in the following cases are shown in Table 1.
[0055] Table 1 Meaning of symbols related to Raman spectroscopy test
[0056]
[0057] 2. Average overpotential test: The cylindrical battery is left at 25°C for 2h, then fully discharged at 0.2C and left to stand for 10 minutes. After that, it is charged to the cut-off voltage at a charging rate of 0.2C, and then charged in constant voltage mode until the current is less than 0.05C. Let it stand for 10 minutes. This step obtains a 0.2C charging curve; thereafter, the same steps are followed for full discharge, and fully charged at different rates (such as 3C rate or 1C rate), and then the constant voltage mode is changed to 0.05C to obtain a series of charging curves. After normalizing the different charging curves according to the horizontal axis SOC, the voltage of each 10% SOC point from 0-100% SOC is subtracted, and the average value is calculated to obtain the average overpotential. The average charging overpotential of the full-ear battery made of the negative electrode sheet at a 3C rate is recorded as φ1, and the average charging overpotential of the negative electrode sheet at a 1C rate is recorded as φ2.
[0058] 3. Calcination test: Take a fresh cylindrical battery, and after standing at 25°C for 2h, fully discharge it with a small current of 0.2C, then disassemble it to get the negative electrode sheet (or directly use the prepared negative electrode sheet), and soak it in DMC for 12h, rinse it with DMC 3 times, and dry it, and further bake it in a 60°C vacuum oven for 2h, then scrape the active material layer on the negative electrode sheet (not less than 8g), accurately weigh it to get the mass M, and then heat it to 350°C at a rate of 10°C / min in a muffle furnace, keep it warm in an air atmosphere for 3 hours, and then naturally cool it to below 50°C, take it out and weigh M', then the loss of the negative electrode active material after calcination can be calculated as m1=M-M', and the corresponding loss rate L=(m1÷M)×100%.
[0059] Example 1
[0060] Negative electrode design
[0061] The negative electrode slurry includes the following solid materials in 100% by weight: 95% of negative electrode active material, 1% of conductive carbon black (with a specific surface area of 65 m 2 / g), single-walled carbon nanotubes 0.50% (aspect ratio 1450, average tube diameter 1.76nm, specific surface area 1069m 2 / g), carboxymethyl cellulose CMC 1.5%, polyacrylic acid PAA 1%, SBR emulsion with a solid content of 40wt%-50wt% 1%;
[0062] The negative electrode active material is a mixture of graphite and silicon-carbon material, and the mass ratio of graphite to silicon-carbon material is 9:1; the surfaces of graphite and silicon-carbon material both have carbon coating layers; the D50 of graphite is 12.4 μm, and the coating amount of the carbon coating layer on the surface of graphite is 4.5 wt%; the D50 of silicon-carbon material is 7.9 μm, and the coating amount of the carbon coating layer on the surface of silicon-carbon material is 5.5 wt%, the carbon coating layer contains silicon-oxygen compounds, and the silicon content in the silicon-carbon material is 49.5 wt%;
[0063] Negative electrode slurry preparation method:
[0064] 1) First, put the silicon-carbon material, conductive carbon black and deionized water into a homogenization tank for premixing, and stir for 10 minutes at a stirring rate of 15 r / min;
[0065] 2) After adding graphite and CMC, continue stirring at a stirring rate of 15r / min for 10min;
[0066] 3) adding single-walled carbon nanotubes and PAA, and adding water until the overall solid content reaches 70 wt%, and stirring at a stirring rate of 30 r / min for 30 min;
[0067] 4) adding water and adjusting the solid content to 65 wt%, and treating for 3 h under the conditions of stirring speed of 15 r / min and dispersion speed of 2000 r / min;
[0068] 5) Add SBR emulsion and water to make the solid content 60wt%, and stop stirring;
[0069] 6) Open the vacuum for 1 h at a dispersion rate of 500 r / min and a stirring rate of 10 r / min;
[0070] The negative electrode slurry prepared above is evenly coated on the surface of the current collector to form a negative electrode active material coating area and a negative electrode active material non-coating area to obtain a negative electrode sheet. The surface density of the coating layer on the surface of the negative electrode sheet is 7.5 mg / cm 2 , the compacted density is 1.6g / cc.
[0071] The positive electrode sheet, the separator and the negative electrode sheet prepared above are wound to form a wound body battery cell, the battery cell is placed in a shell, and the electrolyte is injected to form it, and it is aged at 60° C. for 24 hours to obtain a cylindrical battery.
[0072] According to the above analysis method, the negative electrode was characterized by Raman spectroscopy test, and the 10cm 2 The negative electrode is randomly scanned at 100 test point locations on the electrode. A Raman spectrum is obtained for each location. The wave number of each Raman spectrum is 1000 cm -1 ~2000cm -1The ratio of the strongest peak intensity to the second strongest peak intensity is recorded as Ra, and its reciprocal is recorded as Ra1 (i.e. the ratio of the second strongest peak intensity to the strongest peak intensity), with a wave number of 1450cm -1~ 1800cm -1 The ratio of the strongest peak intensity value to the second strongest peak intensity value is recorded as Rb, and its reciprocal is recorded as Rb1;
[0073] The average value of Ra in 100 location areas is P, and the average value of Rb in 100 location areas is P';
[0074] The average value of the sum of the ratios in the range of 0.1≤Ra1≤1 is P1, and the average value of the sum of the ratios in the range of 1<Ra1≤P is P2; and the number of location areas that meet the condition 0.1≤P1≤1 is counted and recorded as x1, and the proportion of location areas that meet the previous condition is recorded as P1 q , the calculation formula is P1 q =(x1÷n)×100%; the number of location areas that meet the condition 1<P2≤P is recorded as y1, and the proportion of location areas that meet the previous condition is recorded as P2 q , the calculation formula is P2 q =(y1÷n)×100%;
[0075] The average value of the sum of the ratios in the range of 0≤Rb1≤P1 is P1', and the average value of the sum of the ratios in the range of P1<Rb1≤P2 is P2'; and the number of location areas that meet the condition 0≤P1'≤P1 is counted and recorded as x2, and the proportion of location areas that meet the previous condition is recorded as P1' q , the calculation formula is P1' q =(x2÷n)×100%; the number of location areas that meet the condition P1<P2'≤P2 is recorded as y2, and the proportion of location areas that meet the previous condition is recorded as P2' q , the calculation formula is P2' q =(y2÷n)×100%.
[0076] The above statistically obtained P value, P1 value, P2 value, P' value, P1' value, P2' value, P1 q 、P2 q 、P1' q 、P2' q All are in Table 3.
[0077] The cylindrical battery prepared above was also subjected to an average overpotential test and a calcination test (see the analytical method section), and the obtained φ1, φ2, m1, and M are shown in Table 3.
[0078] The main material used in this case is graphite, which has a relatively regular graphite structure, so the ratio of the strongest peak to the second strongest peak in its Raman spectrum is 9.5, while the ratio of the strongest peak to the second strongest peak of the silicon-carbon material after coating is 4.5; the silicon-carbon material and the conductive carbon black are pre-mixed and subjected to the above-mentioned uniform mixing process. At this time, graphite and silicon-carbon materials coexist in some areas, so the strongest peak is graphite, and the second strongest peak is the response of silicon. This part of the signal is also counted, and the average Raman ratio of the obtained pole piece is 7.5. The compaction density is made into 1.6g / cc, and the cold pressing causes the destruction of the local ordered structure, and some particles are broken to reduce the local ratio, and the average value is reduced to P = 6.9. After further high-temperature aging, the P value is reduced to 6.5.
[0079] In the area of the electrode, the Raman response of the area where graphite and silicon-carbon particles are rich is significantly different. The signal intensity of the area where graphite particles are rich and contain a small amount of silicon-carbon is P2, while the intensity of the area where silicon-carbon is rich and cold-pressed, graphite is crushed, and conductive carbon black is rich is P1. In this case, since the main body of the active material is graphite, P2 q The proportion is higher at 37%, while P1 q The ratio of P1 is too high, which leads to low stability. The number of x1 cannot exceed the number of y1, that is, P1 needs to be satisfied. q <P2 q The areas outside the two ratios are dominated by graphite with a larger ratio, and they are orderly and safe, but have kinetic deviations. Therefore, it is necessary to ensure that this part accounts for a high proportion, but not too much. If the proportion of this part is higher than that of the P2 area (more than 20%), it will cause the high-rate performance to deteriorate.
[0080] The end faces of the graphite in this case will show P' signals in the Raman response, and the statistical average is 3.7. The two regions P1' and P2' (i.e. the statistical numbers of x2 and y2) represent the areas where the graphite end faces are slightly exposed and heavily exposed, respectively. In these two regions with different characteristics, P1'q accounts for about 8% and P2'q accounts for about 12%. This area is where the graphite end faces are exposed, and its stability is poor. If the total amount of the two exceeds 50%, the interface stability will be reduced, thus creating a safety hazard.
[0081] The design process of the negative electrode sheet of Examples 2 to 9 and Comparative Examples 1 to 7 is the same as that of Example 1, and the differences are shown in Table 2 below. P value, P1 value, P2 value, P' value, P1' value, P2' value, P1 value obtained by statistics of Examples 2 to 9 and Comparative Examples 1 to 7 q 、P2 q 、P1' q 、P2' qSee Table 3; the cylindrical batteries prepared in each case were subjected to average overpotential test and calcination test (see analysis method), and the obtained φ1, φ2, m1, and M are shown in Table 3.
[0082] Table 2 Design parameters of each case
[0083]
[0084] (Note: √ indicates that the negative electrode slurry preparation method includes step (1); × indicates that the negative electrode slurry preparation method does not include step (1))
[0085] Performance Testing
[0086] The full-ear cylindrical batteries made of negative electrodes designed in the above cases were subjected to rate cycle retention test and overcharge test.
[0087] (1) The test method for rate cycle retention is:
[0088] Take a cylindrical lithium battery prepared according to any of the above embodiments, place it in a 25°C constant temperature box for more than 4 hours, and test it according to the following steps:
[0089] S1: Discharge the battery at a constant current of 0.1C to 2.5V cutoff, and let it stand for 5 minutes;
[0090] S2: Charge the battery at a constant current of 0.2C to a cutoff of 4.2V, and charge it at a constant voltage of 0.05C to a cutoff, and let it stand for 5 minutes;
[0091] S3: Discharge the battery at 0.2C constant current to 2.5V cutoff, and let it stand for 5 minutes;
[0092] S4: Charge the battery at 3C constant current to 4.2V, and charge at constant voltage to 0.05C cutoff, and let it stand for 5 minutes;
[0093] S5: Discharge the battery at 10C constant current until the voltage reaches 2.5V, and let it stand for 5 minutes. Read the capacity value C1 at this time.
[0094] S6: repeat the above steps S4 to S5 for 600 cycles;
[0095] S7: Read the discharge capacity of the 600th battery when it is discharged at a constant current of 10C to 2.5V as C600. The cycle performance of a single battery can be obtained by the ratio of the discharge capacity C600 of the 600th battery when it is discharged at a constant current of 10C to 2.5V and the discharge capacity C1 of the first battery when it is discharged at a constant current of 10C to 2.5V. The rate cycle capacity retention rate is: (C600 / C1)×100%.
[0096] (2) Overcharge test
[0097] Take a cylindrical lithium battery prepared according to any of the above embodiments, place it in a 25°C constant temperature box for more than 4 hours, and test it according to the following steps:
[0098] S1: Discharge the battery at a constant current of 0.1C to 2.5V cutoff, and let it stand for 5 minutes;
[0099] S2: Charge the battery at a constant current of 0.2C to a cutoff of 4.2V, and charge it at a constant voltage of 0.05C to a cutoff, and let it stand for 5 minutes;
[0100] S3: Discharge the battery at 0.2C constant current to 2.5V cutoff, and let it stand for 5 minutes;
[0101] S4: Attach temperature sensing wires to the top, middle and bottom of the battery cell to collect temperature signals
[0102] S5: 3C constant current charging to 6.0V, then switch to constant voltage charging for 1h, sampling interval 1s
[0103] S6: Let stand for 30 minutes
[0104] S7: The battery cell does not catch fire or explode, and the maximum temperature is not higher than 150°C, which is considered passed. After testing 5 battery cells in parallel, the pass rate is calculated.
[0105] The results are shown in Table 3.
[0106] Table 3 Statistical parameters and results of the above cases
[0107]
[0108]
[0109] As can be seen from Table 2 and Table 3, the factors that affect the changes in various statistical values such as P in the design of negative electrode plates include: (1) Material selection: the surface carbon coating content of silicon-carbon materials and graphite, the particle size of graphite and silicon-carbon materials, and the addition ratio of the two; it also includes the specific surface area and addition ratio of conductive carbon black and single-walled carbon nanotubes; (2) Slurry preparation: the parameters of premixing silicon-carbon materials and conductive carbon black in the homogenization stage; (3) Battery cell: aging conditions after formation. Through the above interface design, the electrode has a specific P value, P1 value, P2 value, P' value, P1' value, P2' value, P1 value, P2 ... q 、P2 q 、P1' q 、P2' q ,φ1φ2,m1,and M.
[0110] The present invention counts the Raman points of 100 positions on the pole piece under each pole piece design condition to obtain the corresponding number of Raman spectra, and counts and screens the Raman spectra with a wave number of 1000cm -1 ~2000cm -1 With P, P1, P2, and satisfying the following conditions:
[0111] ①1<P≤10;
[0112] ②0.1≤P1≤1;
[0113] ③1<P2≤P;
[0114] And the wave number in the Raman spectrum is 1450cm -1 ~1800cm -1 With P', the following conditions are satisfied: ④0≤P'≤P; when P'≠0, there are two position areas P1' and P2' with different P' values, and the following conditions are satisfied at the same time:
[0115] ⑤0≤P1'≤P1;
[0116] ⑥P1<P2'≤P2;
[0117] In addition, the proportion of location areas that meet condition ② and condition ③ satisfies the following relationship: P1 q ≤P2 q ≤1.2×(1-P1 q -P2 q ), the proportion of location areas meeting condition ⑤ and condition ⑥ satisfies the following relationship: P1' q +P2' q <50%;
[0118] Based on this, the negative electrode calcination loss rate L satisfies the following relationship: 3%≤L≤20%, and the average charge overpotential φ1 of the lithium-ion battery at a 3C rate satisfies: 0<φ1≤0.5V and the average charge overpotential φ2 of the negative electrode of the battery at a 1C rate satisfies the following relationship: 0<φ2≤0.5φ1. Under these conditions, a lithium-ion battery with high rate charge and discharge can be screened out, and the battery has more excellent safety performance.
[0119] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A lithium-ion battery with excellent rate performance, comprising a negative electrode plate, characterized in that: The wave number of the negative electrode plate in the spectrum is 1000cm -1 ~2000cm -1 With P, P1, P2, and satisfying the following conditions: ①1<P≤10; ②0.1≤P1≤1; ③1<P2≤P; The definition of P is: at least 100 random point scans on the negative electrode are tested by Raman spectroscopy, thereby generating a corresponding number of Raman spectra, and calculating the peaks of each Raman spectrum at a wave number of 1000 cm -1 ~2000cm -1 The ratio of the strongest peak intensity value to the second strongest peak intensity value is recorded as Ra, and the corresponding number of Ra are summed and averaged to obtain P; The definitions of P1 and P2 are: -1 ~2000cm -1 The ratio of the intensity value of the second strongest peak to the intensity value of the strongest peak is recorded as Ra1. The sum and average of the ratios in the range of 0.1≤Ra1≤1 is obtained to obtain P1; the sum and average of the ratios in the range of 1<Ra1≤P is obtained to obtain P2.
2. A lithium-ion battery with excellent rate performance according to claim 1, characterized in that: The wave number of the spectrum is 1450cm -1 ~1800cm -1 With P', the following conditions are satisfied: ④0≤P'≤P; The definition of P' is: Calculate the corresponding number of the Raman spectra obtained above at the wave number 1450cm -1 ~1800cm -1 The ratio of the strongest peak intensity value to the second strongest peak intensity value is recorded as Rb, and the corresponding number of Rb's are summed and averaged to obtain P'.
3. A lithium-ion battery with excellent rate performance according to claim 2, characterized in that: When P'≠0, there are two position areas P1' and P2' with different P' values, and the following conditions are met: ⑤0≤P1'≤P1; ⑥P1<P2'≤P2; Wherein, the definitions of P1' and P2' are: Calculate the corresponding number of Raman spectra obtained above at the wave number 1450cm -1 ~1800cm -1 The ratio of the intensity value of the second strongest peak to the intensity value of the strongest peak is recorded as Rb1. The sum and average of the ratios in the range of 0≤Rb1≤P1 is obtained to obtain P1'; the sum and average of the ratios in the range of P1<Rb1≤P2 is obtained to obtain P2'.
4. A lithium-ion battery with excellent rate performance according to claim 3, characterized in that: Assuming that the number of the at least 100 position areas of the point scan is n, then in the corresponding number of Raman spectra, the number of position areas that meet condition ② is x1, and the number of position areas that meet condition ③ is y1. The proportion of the number of position areas that meet condition ② is recorded as P1 q , the proportion of location areas that meet condition ③ is recorded as P2 q , then P1 q =(x1÷n)×100%, P2 q =(y1÷n)×100%, then the proportion of the number of location areas satisfies the following relationship: P1 q ≤P2 q ≤1.2×(1-P1 q -P2 q ).
5. A lithium-ion battery with excellent rate performance according to claim 3, characterized in that: Assuming that the number of the at least 100 position areas of the point scan is n, then in the corresponding number of Raman spectra, the number of position areas that meet condition ⑤ is x2, and the number of position areas that meet condition ⑥ is y2. The proportion of the number of position areas that meet condition ⑤ is recorded as P1' q , the proportion of location areas that meet condition ⑥ is recorded as P2' q , then P1' q =(x2÷n)×100%, P2' q =(y2÷n)×100%, then the number of location areas satisfies the following relationship: P1' q +P2' q <50%.
6. A lithium-ion battery with excellent rate performance according to any one of claims 1 to 5, characterized in that: The average charge overpotential of the negative electrode plate at a 1C rate is φ2, and φ2 satisfies the following relationship: 0<φ2≤0.5φ1; Wherein, φ1 represents the average charge overpotential of a lithium-ion battery made with the negative electrode sheet at a 3C rate, and φ1 satisfies the following relationship: 0<φ1≤0.5V.
7. A lithium-ion battery with excellent rate performance according to any one of claims 1 to 5, characterized in that: The negative electrode plate comprises a negative electrode current collector and a negative electrode active material coating region and a negative electrode active material non-coating region located on at least one surface of the negative electrode current collector; The negative electrode active material coating area is formed by coating and curing the negative electrode slurry, wherein the negative electrode slurry includes a negative electrode active material, a dispersant, a binder and a conductive agent; The negative electrode active material is selected from one or more of graphite, graphite, mesophase carbon microspheres, hard carbon, soft carbon, and silicon-based materials, and the surface of the negative electrode active material may or may not have a carbon coating layer; The conductive agent is selected from one or more of acetylene black, carbon nanotubes, carbon nanofibers, graphite, graphene, graphene oxide, reduced graphene oxide, and fluorinated graphene.
8. A lithium-ion battery with excellent rate performance according to claim 7, characterized in that: The negative electrode slurry includes solid matter and solvent, and the solid content of the negative electrode slurry is in the range of 30wt%-60wt%; The solid material includes the following materials in 100% by weight: 94%-98.5% of negative electrode active material, 0.5%-2% of conductive agent, 0.5%-2% of dispersant, and 0.5%-2% of binder.
9. A lithium-ion battery with excellent rate performance according to claim 8, characterized in that: The negative electrode active material includes 0%-35wt% of silicon-based material.
10. A lithium-ion battery with excellent rate performance according to claim 9, characterized in that: The negative electrode active material on the negative electrode plate is placed in an air atmosphere and calcined within 350°C. The weight of the negative electrode active material before calcination is M, and the weight of the negative electrode active material after calcination is M'. The loss amount of the negative electrode active material after calcination is m1=M-M', and the corresponding loss rate L=(m1÷M)×100%. The loss rate L satisfies the following relationship: 3%≤L≤20%. 11 . The lithium ion battery with excellent rate performance according to claim 1 , wherein the lithium ion battery is a full-tab lithium ion battery.
12. An electrical device comprising the lithium-ion battery with excellent rate performance according to any one of claims 1 to 11.